The Bloomsbury Handbook of Popular Music Education: Perspectives and Practices - Moir, Zack; Powell, Bryan; Smith, Gareth Dylan (Bloomsbury Publishing Plc, 2019)
The Bloomsbury Handbook of Popular Music Education draws together current thinking and practice on popular music education from empirical, ethnographic, sociological, and philosophical perspectives. Through a series of unique chapters from authors working at the forefront of music education, this book explores the ways in which an international group of music educators each approach popular music education. Chapters discuss pedagogies from across the spectrum of formal to informal learning, including “outside” and “other” perspectives that provide insight into the myriad ways in which popular music education is developed and implemented. The book is organized into the following sections:- Conceptualizing Popular Music Education- Musical, Creative, and Professional Development- Originating Popular Music- Popular Music Education in Schools- Identity, Meaning, and Value in Popular Music Education- Formal Education, Creativities, and Assessment Contributions from academics, teachers, and practitioners make this an innovative and exciting volume for students, teachers, researchers, and professors in popular music studies and music education.